Tenors Not Sopranos: Bio-Mechanical Constraints on Calling Song Frequencies in the Mediterranean Field-Cricket - Jonsson, Thorin; Montealegre-Z, Fernando; Soulsbury, Carl D.; Robert, Daniel (Frontiers in Ecology and Evolution, 2021)
Male crickets and their close relatives bush-crickets (Gryllidae and Tettigoniidae, respectively; Orthoptera, Ensifera) attract distant females by producing loud calling songs. In both families, sound is produced by stridulation, the rubbing together of their forewings, whereby the plectrum of one wing is rapidly passed over a serrated file on the opposite wing. The resulting oscillations are amplified by resonating wing regions. A striking difference between Gryllids and Tettigonids lies in wing morphology and composition of song frequency: Crickets produce mostly low-frequency (2-8 kHz), pure tone signals with highly bilaterally symmetric wings, while bush-crickets use asymmetric wings for high-frequency (10-150 kHz) calls. The evolutionary reasons for this acoustic divergence are unknown. Here, we study the wings of actively stridulating male field-crickets (Gryllus bimaculatus) and present vibro-acoustic data suggesting a biophysical restriction to low-frequency song. Using laser Doppler vibrometry and brain-injections of the neuroactivator eserine to elicit singing, we recorded the topography of wing vibrations during active sound production. In freely vibrating wings, each wing region resonated differently. When wings coupled during stridulation, these differences vanished and all wing regions resonated at an identical frequency, that of the narrow-band song (~5 kHz). However, imperfections in wing-coupling caused phase shifts between both resonators, introducing destructive interference with increasing phase differences. The effect of destructive interference (amplitude reduction) was observed to be minimal at the typical low frequency calls of crickets, and by maintaining the vibration phase difference below 80°. We show that, with the imperfect coupling observed, cricket song production with two symmetric resonators becomes acoustically inefficient above ~8 kHz. This evidence reveals a bio-mechanical constraint on the production of high-frequency song whilst using two coupled resonators and provides an explanation as to why crickets, unlike bush-crickets, have not evolved to exploit ultrasonic calling songs.